Ensiklopedi pemikiran ulama Aceh - Amiruddin, M. Hasbi, 1953-; Shadiqin, Sehat Ihsan, 1979-; Institut Agama Islam Negeri Jamiʼah ar-Raniry. (Banda Aceh, Provinsi Nanggroe Aceh Darussalam : Ar-Raniry Press, 2004)
Encyclopedia of Achinese Muslim leaders and their thoughts on Islamic values related to local tradition in Aceh, Indonesia.
Vol. 3 edited by M. Hasbi Amiruddin and Sehat Ihsan Shadiqin.
Includes bibliographical references and index
Keywords: Muslim scholars -- Indonesia -- Aceh -- Biography; Ulama -- Indonesia -- Aceh -- Biography